Local Cultural Wisdom to Maintain The Existence of Traditional Sports Sumpitan in Samarinda City, East Kalimantan Province - Puji Astuti; Setya Rahayu; Tommy Soenyoto; Priagung Priagung (STKIP Muhammadiyah Kuningan, 2022)
The purposes of this research are to find out how are the conservation efforts, the human resources, the facilities and infrastructure, the process of obtaining the funding and the role of the government/stakeholders in preserving and improving the performance of the traditional sport named Sumpitan. This research is a descriptive qualitative with ethnographic design which using critical ethnography type. The data were collected using interviews, observation and documentation. The subjects of this research include administrators, coaches, athletes and supporting staff, Department of Youth, Sport and Tourism, Department of Education, Indonesian Sport and Recreation Committee (KORMI), Indonesian Traditional Games and Sport Committee (KPOTI) of Samarinda City. The validity of the data was done by implementing some steps including data collection, data reduction, data presentation and draw conclusion. There are several results of the research. Firstly, the Government of the Samarinda City rarely holds Sumpitan traditional sport events, coaching and improvement which have not been included in the local content curriculum of elementary, junior and senior high schools. Next, lack of attention dealing with funding and infrastructure support thus the operational costs use donations from community members. The minimum number of administrators, coaches, and regeneration of new athletes. The last is the lack of public awareness of the improvement and preservation in the implementation of cultural activities or traditional sports Sumpitan. the conclusions of this study are involvement that are not yet optimal, Lack of human resources, there is a change in culture, socio-cultural shift.